1996
DOI: 10.1017/s0950268800001229
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in general population in Madagascar: evidence for different epidemiological patterns in urban and in rural areas

Abstract: SUMMARYTo describe the features of hepatitis B virus (HBV) infection in Madagascar, a randomized sero-epidemiological survey was undertaken in the general population > 1 year old of two provinces which represents 45 % of the total population. In the 921 sera tested, the prevalence of HBV markers was 20-5 % for HBsAg, 38-2 % for anti-HBc and 6-9 % for HBeAg. HBsAg and anti-HBc prevalence rates were significantly higher in males. A large difference in HBsAg prevalence was observed between urban (5 3 %) and rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…In this study, HBV prevalence, defined as recent or past infection, was 35.5% among PW. The result is consistent with HBV epidemiology on Mayotte, the route of HBV transmission being mainly perinatal, from mother to child or from person to person in early childhood [13][14][15][16]20,21,24,25,27,28,[36][37][38][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, HBV prevalence, defined as recent or past infection, was 35.5% among PW. The result is consistent with HBV epidemiology on Mayotte, the route of HBV transmission being mainly perinatal, from mother to child or from person to person in early childhood [13][14][15][16]20,21,24,25,27,28,[36][37][38][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 81%
“…Among PW of Mayotte Island, both qualification and birthplace were significantly associated with HBV vaccination. Birthplace is known to be an important demographic factor linked with the endemicity of HBV infection in these areas [1,3,18,20,21,24,25,27,28,[36][37][38][39][40][41][42][43]. Unemployment and education were other determinants of HBV vaccination, suggesting that education is important in successful HBV vaccination programs [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of a study conducted in rural settings reported a very high prevalence of hepatitis B, with 72.5 to 89.8% of the study population carrying at least 1 marker of the B virus, and with 18.9 to 30.5% of HBsAg carriers [7]. Boisier et al reported an overall Hepatitis B prevalence of 5% in urban areas and 25% in rural areas [8]. Little data was available on pregnant patients in Madagascar and published data was too old to allow comparing results.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study, therefore, was to sequence and characterize the complete genome of genotype E isolates obtained from geographically distinct regions in Africa, namely, Namibia, Angola, and Madagascar. High HBV carrier rates have been recorded in all three countries: 15% in Namibia [Botha et al, 1984], 13% in Angola [Steele and Bos, 1996], and 26% in Madagascar [Boisier et al, 1996].…”
Section: Introductionmentioning
confidence: 99%